Exploring the Differential Associations between Components of Executive Functioning and Reactive and Proactive Aggression - Hecht, Lisa (2015)
The current study explored the nuanced associations between components of executive functioning (EF) and subtypes of aggression, using a latent variable approach. Participants were racially diverse undergraduate students who completed a self-report of reactive (RA) and proactive aggression (PA), and traditional neuropsychological tasks of EF. The appropriateness of using a nested bifactor model of EF was confirmed, and this bifactor model of EF was used to examine the specific associations between components of EF and RA and PA. Results revealed components of EF are differentially associated with RA and PA, such that impulsive, provoked aggression is associated with lower levels of goal-oriented inhibition and higher levels of flexibility, whereas planned, goal-oriented aggression is associated with higher levels of working memory. Findings from the current study underscore the importance of considering the multidimensional nature of EF as well as aggression when examining their associations with external constructs of interest